Parameters Influencing the Growth of ZnO Nanowires as Efficient Low Temperature Flexible Perovskite-Based Solar Cells - Dymshits, Alex (Materials (Basel), 2016)
Hybrid organic-inorganic perovskite has proved to be a superior material for photovoltaic solar cells. In this work we investigate the parameters influencing the growth of ZnO nanowires (NWs) for use as an efficient low temperature photoanode in perovskite-based solar cells. The structure of the solar cell is FTO (SnO(2):F)-glass (or PET-ITO (In(2)O(3)·(SnO(2)) (ITO)) on, polyethylene terephthalate (PET)/ZnAc seed layer/ZnO NWs/CH(3)NH(3)PbI(3)/Spiro-OMeTAD/Au. The influence of the growth rate and the diameter of the ZnO NWs on the photovoltaic performance were carefully studied. The ZnO NWs perovskite-based solar cell demonstrates impressive power conversion efficiency of 9.06% on a rigid substrate with current density over 21 mA/cm(2). In addition, we successfully fabricated flexible perovskite solar cells while maintaining all fabrication processes at low temperature, achieving power conversion efficiency of 6.4% with excellent stability for over 75 bending cycles.